(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In the context of transnational families, especially among the Indian diaspora, elderly parents often experience emotional isolation due to physical separation from their children. This study explores how digital communication technologies—such as video calls, messaging apps, and social media serve as tools of virtual caregiving, offering emotional support and a sense of connection. Using a narrative approach, this research analyzes the lived experiences of elderly parents left behind in India to understand how they perceive, engage with, and are impacted by these virtual interactions. The findings reveal that while digital communication mitigates loneliness and fosters emotional reassurance, it also exposes gaps in digital literacy and emotional fulfillment. This article argues that virtual caregiving, though not a substitute for physical presence, has become an essential component of modern eldercare in diasporic contexts.